KAJIAN TINGKAT KEMISKINAN DI KAWASAN IRIGASI ULEE JALAN KABUPATEN NAGAN RAYA - Dewi Fithria (Jurnal Bisnis Tani, 2016)
In 2009 the production of rice plant in Nagan Raya district totaled 100.135 tons of grain. This figure has risen by 57.99 percent compared to its 2008 production reached 63.382 tons of grain. This increase was caused by the increase of rice planting area of 14 097 hectares in 2008 become be as 20.027 hectares in 2009. However, the increase in rice production is not significant to the income of farmers. The purpose of this study was to determine the level of income, income distribution and poverty levels of farm households, as well as the factors affecting the level of poverty. This research was conducted in the area of irrigation Ulee Jalan Nagan Raya which is divided into three parts, namely the upstream, midstream and downstream. The results showed that there were poor farming households in the upstream part of (36.52%), middle (33.33%), and downstream (40.48%), and poverty are serious enough indicated by the headcount index of more than 30%, poverty gap index respectively by 0.09, 0.13 and 0.10 indicating that farmer households still need additional substantial resources.The results of this study indicate land area, the outpouring of labor (employment) outside the farm, farm income, and sufficient supply of irrigation water is the dominant factor in reducing household poor farmers in irrigated areas.